Effects of water level changes on the hydrological connectivity and water quality of a lake-type wetland - Lin, Yemiao; Dai, Junfeng; Peng, Xinyue; Li, Zheqing; Wan, Zupeng (Frontiers in Environmental Science, 2025)
IntroductionUnderstanding the effects of water level fluctuations on wetland ecosystems is crucial for water resource management and ecological conservation. While there have been some studies on this topic, comprehensive analyses of how water level changes affect the hydrological connectivity and water quality of complex lake-type wetlands remain relatively limited. This work aims to explore the effects of water level changes on the connectivity and water quality of lake-type water bodies in the Huixian Karst Wetland, Guilin.MethodsWater quality data for Mudong Lake from January 2021 to December 2022 were obtained by collecting monthly water samples and conducting laboratory tests for six common water quality parameters. Through a combination of remote sensing image data, drone image data and actual measured data on the Mudong Lake water level, the comprehensive ecological-hydrological connectivity index and comprehensive water quality index were used to evaluate the water level changes in Mudong Lake, water body connectivity, and water quality. The correlations between them were then analysed.ResultsThe results show that as the water level increases, the degree of landscape fragmentation decreases, and the water connectivity index increases by 262%. In addition, as the water level increases, the comprehensive water quality pollution index shows an overall downward trend.DiscussionHowever, the factors affecting lake water quality are complex and changeable. Future research could consider increasing the monitoring frequency during critical periods of rapid hydrological change, such as rainfall-runoff events, to capture more precise and detailed hydrological and water quality data. This study provides an important example of the effects of changes in water level and wetland connectivity on the water quality of a lake ecosystem.